Experiência com geometria dinâmica no ensino fundamental - Oliveira, Waldemir Campos de (2015)
This Assignment has as aim introduce the study of Geometry with the computers resoursers to softwares of GeoGebra dynamic Geometry. The idea is organize a Project, for the Maths teachers to the elementarY school, can use to develop activities in the computers room using basics resoursers to the syllabuses explained for investigations, find the definitions and geometrical propeties and put in the same exhibition classes, so that the students can see and to get used with these geometrical knowledge, plans of Maths.